THE CHARACTERISTIC OF WATER QUALITY AT BATUR LAKE, KINTAMANI DISTRIC, BALI PROVINCE - Arthana, I Wayan (Bumi Lestari; Vol 11 No 1 (2011), 2011)
Batur Lake located at Kintamani district, Bangli regency is the biggest lake in Bali that is very important as water stocking for Bali area. Collecting samples at 50 substations was done from June up to October 2009. Temperature value at Batur Lake varied of 23 °C - 25 °C with average of 23.88 °C. The water clarity was around 1.58 - 2.90 meter with the average of 2.32 meter. The average value of water quality of BOD5 and COD were 3.817 ppm and 6.333 ppm respectively. The average content of ammonia was 0.4545 ppm and for Sulfide was 0.0009 ppm. The nutrient content in Batur Lake is that nitrate value varied of 0.0174 - 3.6070 ppm with average of 1.1498 ppm. Phosphate content was from no detection up to 0.3610 ppm with the average of 0.1242 ppm. Heavy metals, the average content of Cd, Pb, Cu and Fe were 0.0038 ppm, 0.0023 ppm, 0.0055 ppm and 0.0428 ppm respectively. There is a strong positive correlation between COD and BOD5 that the higher content of the COD the higher BOD5 content as well with correlation value of R2 = 0.927. The ratio value between COD and BOD5 (COD/ BOD5) varies of 1.061 – 12.163 with the average value of 2.492 ± 1.909.
Keywords: lakes, heavy metals, water quality, phosphate, nitrate